Rancang Bangun Sistem Informasi Penggajian Karyawan PT. Boetomix Nusantara Lestari Berbasis WEB - Rohmat Taufiq; Rika Rahmawati; Syepry Maulana Husain; Andhi Setiawan (Teknik Informatika Universitas Pamulang, 2021)
Design of payroll information systems and requests for funds to the company PT. Boetomix Nusantara Lestari WEB-based still uses Microsoft Excel. By using MS Excel, errors that occur in inputting data and requesting payroll data have many errors. The process of sending goods data still uses whatsapp, because whatsapp used by the salary recapitulation officer has difficulty at the end of every month. This application designed has the aim of providing convenience for users so that the recitation process at PT. Boetomix Nusanara Lestari can run quickly and has a high level of accuracy. Interviews, observations and document analysis are methods used in the data collection process. Unified Modeling Language (UML) is used to describe running business processes and the relationship between users and the system. The employee payroll information system has been tested and the results are in accordance with the needs of PT. Boetomix Nusanara Lestari.